PENGARUH MOTIVASI DAN KEDISIPLINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PT.FUMIRA SEMARANG - Sony Adi Pamungkas; Rhodiyah Rhodiyah; Reni Shinta Dewi (Universitas Diponegoro, 2013)
This study aimed to identify the influence of motivation and discipline on employee productivity of production department PT.FUMIRA Semarang. This study used an explanatory research approach to the 83 respondents to the census approach. The data were analyzed qualitatively and quantitatively using test validity, reliability testing, cross-table analysis, the correlation coefficient, simple linear regression, multiple linear regression, the coefficient of determination, t test and F test with tools SPSS 18 for windows. The results obtained are the motivation and discipline, positive impact on employee productivity, and discipline variables are variables that affect the greatest impact on employee productivity.